Optimalisasi pembelajaran bahasa Arab melalui homeschooling: Fleksibilitas waktu pembelajaran bahasa Arab yang disesuaikan dalam homeschooling - Hamdiyah, Heni (Maliki Interdisciplinary Journal, 2024)
Arabic language learning at the elementary and secondary education levels faces various challenges, particularly in terms of effective teaching methods and time limitations. In this context, homeschooling offers a flexible solution that can be tailored to meet the individual needs of students. This article aims to explore how homeschooling can be optimized for Arabic language learning, highlighting the aspects of time flexibility and material customization according to students' proficiency levels. The study examines various teaching strategies that can be applied in a homeschooling environment, such as the use of digital resources, project-based approaches, and the active role of parents in supporting the learning process. Additionally, the article discusses the benefits and challenges associated with the implementation of homeschooling for Arabic language learning, with a focus on the effectiveness of customized methods. The expected outcome of this research is a better understanding of the potential of homeschooling in enhancing Arabic language proficiency in a more personalized and optimal way.